2018
DOI: 10.3389/fpsyg.2018.02082
|View full text |Cite
|
Sign up to set email alerts
|

The Principles of Art Therapy in Virtual Reality

Abstract: In recent years, the field of virtual reality (VR) has shown tremendous advancements and is utilized in entertainment, scientific research, social networks, artistic creation, as well as numerous approaches to employ VR for psychotherapy. While the use of VR in psychotherapy has been widely discussed, little attention has been given to the potential of this new medium for art therapy. Artistic expression in VR is a novel medium which offers unique possibilities, extending beyond classical expressive art medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 62 publications
(66 reference statements)
1
51
0
1
Order By: Relevance
“…Overall, the participants described a sense of increased confidence in using the virtual tools to create imagery during the second session. In previous studies, we have participants reporting references on self-reflection (Hacmun et al, 2018;Kaimal et al, 2019) and unique perspectives, which was further confirmed in the creative expressive tasks in this study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Overall, the participants described a sense of increased confidence in using the virtual tools to create imagery during the second session. In previous studies, we have participants reporting references on self-reflection (Hacmun et al, 2018;Kaimal et al, 2019) and unique perspectives, which was further confirmed in the creative expressive tasks in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Therapeutically, VR can be used for receptive experiences like reflection and meditation in a new immersive environment or for creative self-expression using VR-specific painting and sculpting tools. Hacmun et al (2018) highlight that VR can promote a sense of presence and allows for transformations of the sense of self. Despite the absence of physical art materials, the embodied environment that VR offers can enhance the participant's presence within the artwork.…”
Section: Digital Artmaking and Vr In Art Therapymentioning
confidence: 98%
See 3 more Smart Citations